The Assessment Of Sediment Contamination Level In The Lampung Bay, Indonesia: Heavy Metal Perspective - Fitri Budiyanto; Lestari - (Pusat Riset Kelautan, 2015)
The potency and utilization of Lampung Bay has been recognized for their socio-economical and ecological values. However, heavy use of this Bay may alter the abundance of hazardous chemical like heavy metals. The aims of this study were to determine the concentration of Cd, Cu, Pb and Zn in the sediment and to assess Lampung Bay water condition. The observation of heavy metal content in sediment of Lampung Bay was conducted at 13 stations in March 2008. Analysis of heavy metals in sediment was conducted using three kinds of acid: HNO3, HCl and H2O2 while measurement was carried out by Atomic Absorption Spectrophotometer. The result indicated a variation of heavy metal concentration in sediment and that concentrations of Cd, Cu, Pb and Zn in sediment were 0.08 mg/kg dry weight, 22.99 mg/kg dry weight, 24.75 mg/kg dry weight and 118.48 mg/kg dry weight, respectively. Factors influenced heavy metal concentration in sediment in this study including the distance between sampling location and anthropogenic activities and the sediment fraction SQG-Q index indicated that 7 stations have SQG-Q ≤ 0.1 whereas other 6 stations have 0.1≤ SQG-Q <1, meaning that more than half sampling stations are in uncontaminated state.